The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5539/elt.v12n6p87
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self-Regulations and Online Learning in an ESL Blended Learning Context

Abstract: Technology has changed the social landscape and the nature of social interaction. Education has been affected by these changes, as technology has facilitated the creation and Implementation of new educational environments and delivery methods (e.g., distance and blended-learning structures). While the prevalence of such approaches has increased over time, little is known about the learning skills that promote academic success; consequently, the ability of instructors and administrators to implement appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 8 publications
(15 reference statements)
0
17
0
4
Order By: Relevance
“…Further, online asynchronous learning platforms allow learners to access at their own pace. [36] His study further explained that online environments provided intrinsic goal orientation, self-efficacy for learning, and increased performance. [6] argues that "students who utilize e-learning platforms for learning are usually drawn into the subject matter at a deeper level due to the discussions they get involved in'' (p. 55).…”
Section: Students' Perceptions Of Online Learningmentioning
confidence: 96%
“…Further, online asynchronous learning platforms allow learners to access at their own pace. [36] His study further explained that online environments provided intrinsic goal orientation, self-efficacy for learning, and increased performance. [6] argues that "students who utilize e-learning platforms for learning are usually drawn into the subject matter at a deeper level due to the discussions they get involved in'' (p. 55).…”
Section: Students' Perceptions Of Online Learningmentioning
confidence: 96%
“…Any educator must motivate their students properly, or better yet, make the students motivate themselves. Considerable research related to self-regulation showed that pre-service teachers could do it (Fadda, 2019). If the teachers do not know how to motivate themselves, they may find it difficult to motivate others.…”
Section: Discussionmentioning
confidence: 99%
“…Research regarding the first category would investigate if the students displayed self-regulatory characteristics (Fadda, 2019) or the effectiveness of self-regulation in learning (Vasu, Mei Fung, Nimehchisalem, & Rashid, 2020). On the other hand, research regarding the second category would see how the students self-regulate themselves when exposed to a new skill (Fathi, Ahmadnejad, & Yousofi., 2019).…”
Section: Self-regulation In Esl Classesmentioning
confidence: 99%
“…The following aspects are rated as essential for successful distance learning in the literature (Al Fadda, 2019;Hong and Jung, 2011;Ng, 2019):…”
Section: Literature Reviewmentioning
confidence: 99%